Spatiotemporal analysis of encroachment on wetlands : hazards, vulnerability and adaptations in Kampala City, Uganda - Isunju, John Bosco (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.